A guaranteed basic income and the aesthetics of existence. Issue 1 (2nd January 2019) - Jenkins, Barbara
ABSTRACT: The recent implementation of various guaranteed basic income (GBI) trials presents an opportunity to consider how such policies should be evaluated. If past experience is any guide, they will be judged primarily on the basis of quantitative factors such as cost and labour market impact. While these considerations remain relevant, some of the most transformative aspects of a GBI will happen at the 'aesthetic' level of affect, sensibilities, and attitudes. Using an ethico-aesthetic approach drawing on the work of Foucault, Guattari, Deleuze, and Lazzarato, I examine the dynamic, interactive impact a GBI could have on conceptions of work, welfare and gender. I argue that a GBI can be a key component of a new aesthetic of existence based on a critical ethics of self care.